Dual Drivers of Excellence: How Principal's Leadership and Motivation Shape Teachers’ Performance - Harahap, Muhammad Junaidi; Kristiawan, Muhammad; Eddy, Syaiful (Journal of Social Work and Science Education, 2025)
This study examines (1) the influence of principal leadership, (2) principal work motivation, and (3) their combined effect on high school teacher performance in Babat Toman District. A quantitative approach was employed, collecting data via questionnaires from all 76 high school teachers in the district (proportional random sampling). Data were analyzed using SPSS, including normality, linearity, and homogeneity tests, followed by multiple linear regression (t-test, F-test, and r² analysis). The study revealed: (1) Principal leadership significantly improves teacher performance (t=36.886, p=0.02); (2) Work motivation similarly enhances performance (t=26.703, p=0.017); and (3) Both factors jointly exert a strong influence (F=672.870 > F-table=3.120), explaining a substantial variance in outcomes. This research uniquely quantifies the dual impact of leadership and motivation on teacher performance in a rural Indonesian context, providing empirical validation of their synergistic relationship. Schools should prioritize leadership training and motivational programs for principals, as their decisions and approaches directly shape teacher effectiveness. The study offers a replicable model for evaluating leadership-motivation dynamics in education, serving as a benchmark for policymakers and administrators aiming to optimize teacher performance through principal development.